Pengembangan Materi Kimia Kayu dan Pulp Pada Sub Materi Pohon Untuk Mahasiswa Program Studi Pendidikan Kimia - Seren Nabila; Sanjaya, Sanjaya; Sari, Diah Kartika (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this development research is to produce wood and pulp chemistry teaching materials on tree sub-materials that meet valid criteria. The procedure for developing teaching materials follows the stages in the 4STMD (four-step teaching material development) , starting from the selection stage to the characterization stage. Data collection techniques carried out in this development research were interviews, questionnaires, and walkthroughs. The data analysis technique in this development research uses Aiken's Validity formula to calculate the validity of the material. The results of this study are wood and pulp chemistry teaching materials in the tree sub-material as a supplement to teaching materials for students of the Chemical Education Study Program, Sriwijaya University which has a validity level in the material aspect of 0.86 which is included in the high category. Validity results are obtained by referring to Aiken's validity criteria. The results of the research conducted showed that the development of wood and pulp chemicals in tree sub-materials as a supplement to teaching materials met the valid criteria.